Analysis of sucrose addition on the physicochemical properties of blueberry wine in the main fermentation - Liu, Junbo; Wang, Qian; Weng, Liping; Zou, Ligen; Jiang, Huiyan; Qiu, Jing; Fu, Jiafei (Frontiers in Nutrition, 2023)
Harvested blueberries can be processed into wine to extend their shelf life and increase their commercial value. In order to produce fruit wine, external sugar is often added prior to fermentation to increase the final alcohol content to a target of 8-12% (v/v) to meet consumer expectations. Here, we explore the effect of 8-14 % (w/w) sucrose on the physicochemical properties of blueberry wine throughout the main fermentation process. We monitor changes of alcohol content, sugar, color, phenol, acidity, anthocyanin, and flavor. We notice that sucrose affects the fermentation process and physicochemical composition of the final blueberry wine in several important ways. Additional sucrose extends the total time of fermentation, and increases wine acidity. The color of the wine is also affected, with added sugar darkening and yellowing the final product. Interestingly, the sucrose has a protective effect on anthocyanin levels, although total anthocyanin levels are still substantially reduced following fermentation. Finally, the additional sugar increases accumulation of volatile flavor components, particularly alcohols and esters, as measured by an electronic nose. We conclude that an addition of 12% sucrose produces wine with superior physicochemical properties of alcohol, anthocyanin loss and flavor relative to other conditions tested and recommend this approach to commercial manufacturers.